(untitled) (Research, Society and Development, 2025)
Considering that animal self-medication, or zoopharmacognosy, consists of the use of natural substances with medicinal properties by non-human organisms, and that such behavior is widely documented in primates and birds but rarely in carnivorous mammals, the present study seeks to fill this gap. The objective is to describe the first record of self-medication behavior in the crab-eating fox (Cerdocyon thous) observed in a peri-urban environment in the municipality of Franca, São Paulo, Brazil. To this end, a non-invasive observational study was conducted using a camera trap installed for 15 consecutive days, with photographic and video records analyzed qualitatively. Two distinct episodes of non-feeding manipulation of insects were observed: body rubbing against an orthopteran and repeated licking of a blattodean, both without apparent ingestion. These behaviors exhibited characteristics consistent with topical self-medication mediated by bioactive compounds of entomological origin. This finding broadens the understanding of the phylogenetic scope of zoopharmacognosy and contributes to the comprehension of behavioral sanitary defense strategies in Neotropical canids, highlighting the importance of further studies integrating chemical analyses and prolonged observations in different ecological contexts.